Curcumin, thymoquinone, and 3, 3′-diindolylmethane combinations attenuate lung and liver cancers progression - Saddiq, Amna A.; El-Far, Ali H.; Mohamed Abdullah, Shymaa Abdullah; Godugu, Kavitha; Almaghrabi, Omar A.; Mousa, Shaker A. (Frontiers in Pharmacology, 2022)
Cancer can develop due to abnormal cell proliferation in any body’s cells, so there are over a hundred different types of cancer, each with its distinct behavior and response to treatment. Therefore, many studies have been conducted to slow cancer progression and find effective and safe therapies. Nutraceuticals have great attention for their anticancer potential. Therefore, the current study was conducted to investigate the anticancer effects of curcumin (Cur), thymoquinone (TQ), and 3, 3′-diindolylmethane (DIM) combinations on lung (A549) and liver (HepG2) cancer cell lines’ progression. Results showed that triple (Cur+TQ+DIM) and double (Cur+TQ, Cur+DIM, and TQ+DIM) combinations of Cur, TQ, and DIM significantly increased apoptosis with an elevation of caspase-3 protein levels. Also, these combinations exhibited significantly decreased cell proliferation, migration, colony formation activities, phosphatidylinositol 3-kinase (PI3K), and protein kinase B (AKT) protein levels with S phase reduction. Triple and double combinations of Cur, TQ, and DIM hindered tumor weight and angiogenesis of A549 and HepG2 implants in the chorioallantoic membrane (CAM) model. Interestingly, Cur, TQ, and DIM combinations are considered promising for suppressing cancer progression via inhibiting tumor angiogenesis. Further preclinical and clinical investigations are warranted.